2005
DOI: 10.2188/jea.15.146
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria is a Prognostic Marker for Cardiovascular Mortality: NIPPON DATA 80, 1980-1999

Abstract: Proteinuria or urinary albumin has been considered to be a prognostic marker for patients with non-insulin-dependent diabetes mellitus 1-14 and those with hypertension 10,15-18 or acute myocardial infarction. 19 However, in general population, knowledge about the relationship between proteinuria and mortality is limited. 14 Proteinuria has been a predictor of mortality in subjects aged 65-79 years 20 but not among those 80 years and older. 21 Urinary albumin is related to risk factors for cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 27 publications
3
32
1
1
Order By: Relevance
“…14,15 Because the kidneys provide a significant route for clearance of methylarginines, 16,17 it is perhaps not surprising that ADMA 18 and SDMA concentrations increase in CKD patients even without proteinuria, 19,20 or that proteinuria with reduced renal function is associated with both elevated ADMA and endothelial dysfunction. 10,21,22 However, the patients in our study all had a nearly normal renal function. Inflammation, defined here as an elevated serum hsCRP, is also known to influence ADMA and has been proposed to be one factor linking ADMA to CVD.…”
Section: Discussionmentioning
confidence: 63%
“…14,15 Because the kidneys provide a significant route for clearance of methylarginines, 16,17 it is perhaps not surprising that ADMA 18 and SDMA concentrations increase in CKD patients even without proteinuria, 19,20 or that proteinuria with reduced renal function is associated with both elevated ADMA and endothelial dysfunction. 10,21,22 However, the patients in our study all had a nearly normal renal function. Inflammation, defined here as an elevated serum hsCRP, is also known to influence ADMA and has been proposed to be one factor linking ADMA to CVD.…”
Section: Discussionmentioning
confidence: 63%
“…The small, but steady, percentage that continued to be exposed to immunosuppression over the observation period would suggest that this message needs to be emphasized. Again, although not proven by this study, conservative therapy including treatment of hypertension to lower BP targets (Ͻ130/80 mmHg) along with smoking cessation and treatment of hypercholesterolemia to LDL targets Ͻ2 mmol/L would seem prudent given the established risk factor of proteinuria in cardiovascular disease (23)(24)(25).…”
Section: Discussionmentioning
confidence: 79%
“…[31][32][33] Long-term trials have indicated an antiproteinuric effect of losartan. [33][34][35][36] In this study, the 3-month treatment with 100 mg losartan failed to show a significant UACR reduction in patients with morning hypertension (Figure 4a).…”
Section: Discussionmentioning
confidence: 99%